CO2-on-a-Chip: Current Status and Prospects of Carbon Dioxide Microfluidic Technology - Zhang Yinglong; Chen Qinglin; Hu Jie; Xin Gongming; Gong Weiping; Zhao Pei; Qin Ning (Zhileng xuebao)
Microfluidics is of great importance in investigating the various physicochemical processes of carbon dioxide, the latter of which plays a fundamental role in the carbon capture, utilization, and storage (CCUS) process, as well as in achieving the goals of carbon peaking and neutralization. Here, the current status of carbon dioxide microfluidic technology, that is, the CO2-on-a-chip technology, is reviewed. CCUS technology and some basic aspects of microfluidics are briefly introduced. In particular, the advantages and impacts of microfluidic technology in advancing CO2-related studies are discussed. Examples of applications and research progress of microfluidics in screening solvents for CO2 capture, supercritical CO2-based extraction, enhanced oil recovery by CO2, biochemical conversion of CO2, and CO2 storage are specifically introduced. Finally, the success of applying microfluidics to CO2 is summarized, and the future development of this area is envisioned.